Comments on "A fuzzy approach to strategic games". - Mathew, R. (IEEE Transactions on fuzzy systems)
A fuzzy approach was proposed in the above paper for the solution of strategic games and some useful conclusions were presented on the selection of optimal strategies in the prisoner's dilemma game. In this paper, a general result is presented for the case in which a prisoner is noncooperative and selfish, which makes the evaluation suggested in the above paper redundant in this case.